KEPUASAN AKSEPTOR KB TERHADAP PELAYANAN KB DI BIDAN SURATMI KOTA BATAM - Nova Roza; Silvia Mona (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2022)
Family planning services strongly emphasize the demographic aspect, namely birth control one of the main aspects in the family planning program is the quality of services provided. Improved service quality will increase the number of satisfied family planning participants and will increase the prevalence and decrease the birth rate (BKKBN, 2015). The design used in this study is a descriptive design that aims to identify the satisfaction of family planning acceptors in family planning services at the Midwifery Suratmi 2022. The sample in this study amounted to 96 people. The sampling technique in this study was accidental sampling. The results of respondents' answers on family planning services, then divided into 3 categories, namely categories of high levels of satisfaction, moderate levels of satisfaction and low levels of satisfaction. The data obtained shows that people (79%) acceptors who have a high level of satisfaction, (18%) acceptors who have a moderate level of satisfaction and (2%) acceptors who have a low level of satisfaction with family planning services. This study shows that the satisfaction of family planning acceptors in family planning services, the majority of the level of satisfaction of acceptors in the medium category.